Body Size Plasticity of Weevil Larvae (Curculio davidi) (Coleoptera: Curculionidae) and Its Stoichiometric Relationship With Different Hosts. Issue 1 (4th January 2021) - Du, Baoming; Yuan, Jun; Ji, Huawei; Yin, Shan; Kang, Hongzhang; Liu, Chunjiang
Abstract: Parasites obtain energy and nutrients from the host, and their body size is also usually limited by host size. However, the regulatory mechanisms that control the plasticity of parasite body sizes and the stoichiometric relationships with their hosts remain unclear. Here we investigated the concentrations of 14 elements (C, H, O, N, P, S, K, Na, Ca, Mg, Al, Fe, Mn, and Zn) in the acorns of three oak species ( Quercus spp.), in their endoparasitic weevil ( Curculio davidi Fairmaire) (Coleoptera: Curculionidae) larvae and in the larval feces, and the weight of weevil larvae within different hosts in a warm-temperate zone of China. Our results showed that the three acorn species exhibited significant differences in C, H, O, P, K, Mg, and Mn concentrations. However, in the weevil larvae, only P, Mn, and C:P ratio revealed significant differences. Weevil larvae preferentially absorbed and retained N, Zn, Na, and P, whereas Mn, K, Ca, and O were passively absorbed and transported. The weevil larvae weight was associated with acorn stoichiometry, and positively correlated with acorn size. Weevil larvae P decreased, but Mn and C:P increased with their weight, implying highly variable in somatic stoichiometry are coupled with the plasticity of body size. Interestingly, weevil larvae weight was negatively correlated with acorn infection rate, indicating small-size parasitic insects might have higher fitness level in parasite–host systems than larger-size ones. Our results suggest that variation in P, Mn, and C:P in parasites may play critical roles in shaping their body size and in improving their fitness.